Regulation of adult stem cell function by ketone bodies - Andersen, Ole Emil; Poulsen, Jens Vase; Farup, Jean; de Morree, Antoine (Frontiers in Cell and Developmental Biology, 2023)
Adult stem cells play key roles in tissue homeostasis and regeneration. Recent evidence suggests that dietary interventions can significantly impact adult stem cell function. Some of these effects depend on ketone bodies. Adult stem cells could therefore potentially be manipulated through dietary regimens or exogenous ketone body supplementation, a possibility with significant implications for regenerative medicine. In this review we discuss recent findings of the mechanisms by which ketone bodies could influence adult stem cells, including ketogenesis in adult stem cells, uptake and transport of circulating ketone bodies, receptor-mediated signaling, and changes to cellular metabolism. We also discuss the potential effects of ketone bodies on intracellular processes such as protein acetylation and post-transcriptional control of gene expression. The exploration of mechanisms underlying the effects of ketone bodies on stem cell function reveals potential therapeutic targets for tissue regeneration and age-related diseases and suggests future research directions in the field of ketone bodies and stem cells.